Differences in luxury value perceptions and purchase intentions among different generations of Chinese consumers - Li, Weiran (2022)
The personal luxury goods market in China is a large and promising one. As a result of the outbreak of the Covid-19 pandemic, the Chinese personal luxury goods market experienced two years of depression. At the start of 2022, the Chinese personal luxury market bottomed out and returned to pre-Pandemic Covid-19 sales levels. Some experts expect China's personal luxury market to become the world's largest dominant market by 2025. The Chinese luxury consumer is the absolute force behind this success. However, there are currently two research gaps in the study of Chinese luxury consumption. The first is the focus on Chinese millennial luxury consumers to the detriment of the youngest generation of consumers. The second is that research on Chinese generational consumers is based on Western generational divisions and does not differentiate generational consumers according to the Chinese context. Therefore, in order to remedy these shortcomings, this study names the two younger generations of Chinese luxury consumers as the emperor generation and the globalised generation respectively, taking the major events in Chinese history as the dividing point, not only studying the emperor generation but also providing a perspective on the consumption of the youngest leading consumer force, the globalised generation. In terms of the theoretical framework, this study combines the luxury value perception framework to explore how the two generations of Chinese luxury consumers understand the value of luxury in terms of three dimensions: social value, personal value, and functional value of luxury. Using generations as a mediator, the link between value perception and purchase intention is established. This study will not only test the applicability of luxury value perception theory in the Chinese market but also identify the drivers of purchasing behaviour of Chinese luxury consumers across generations.